2014
DOI: 10.1111/nan.12044
|View full text |Cite
|
Sign up to set email alerts
|

Fungal encephalitis in human autopsy cases is associated with extensive neuronal damage but only minimal repair

Abstract: Unlike in other infectious diseases of the nervous system where a coexistence of damage and repair was observed, fungal encephalitis is characterized by strong damage and minimal neuronal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
0
18
1
Order By: Relevance
“…The density of apoptotic neurons in HIV encephalopathy was comparable to the density in fungal encephalitis (median = 19.4 cells/mm 2 ) [22], but higher than in septic‐metastatic encephalitis (median = 9.2 cells/mm 2 ) [17] and bacterial meningitis (median = 3 cells/mm 2 ) [16] as assessed using the same method. This suggests severe hippocampal injury and is probably an important morphological correlate of the decline in learning and memory in HIV‐infected patients [26].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The density of apoptotic neurons in HIV encephalopathy was comparable to the density in fungal encephalitis (median = 19.4 cells/mm 2 ) [22], but higher than in septic‐metastatic encephalitis (median = 9.2 cells/mm 2 ) [17] and bacterial meningitis (median = 3 cells/mm 2 ) [16] as assessed using the same method. This suggests severe hippocampal injury and is probably an important morphological correlate of the decline in learning and memory in HIV‐infected patients [26].…”
Section: Discussionmentioning
confidence: 70%
“…The number of lesions with acute axonal damage (a lesion was defined as a locally restricted accumulation of APP‐positive axons) was converted into a semiquantitative score: 0 points for no damage or just single injured axons, 1 point for mild damage (one or two lesions), 2 points for moderate damage (three or four lesions) and 3 points for severe damage (more than four lesions) [17,22]. Microglial activation as well as astrocytosis in the frontal cortex was categorized in three groups according to the density of immunoreactive cells and converted into a semiquantitative score: 1 point for < 10 Iba‐1‐immunoreactive cells, 2 points for ≥ 10 and < 30 Iba‐1‐positive cells, and 3 points for ≥ 30 Iba‐1‐positive cells at 20x magnification in three random regions in the frontal cortex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the altered and/or damaged state of the BBB along with changes in homeostatic interactions between the BBB, astrocytes, and neurons (i.e., the neurovascular unit) may contribute to long‐term cognitive deficiencies (Grab, Chakravorty, van der Heyde, & Stins, ). In a recent study, 15 autopsy cases of men and women with neuropathologically and microbiologically confirmed fungal infections of the brain found that compared to bacterial meningitis and septic encephalitis, fungal encephalitis was characterised by a strong microglial activation and astrocyte proliferation, more neuronal damage, and less endogenous repair (Tauber et al, ). These findings indicated severe damage to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated severe damage to the brain. Unlike in other infectious diseases of the CNS, where a coexistence of damage and repair was observed, fungal encephalitis was characterised by axonal injury, astrocytosis, microglial activation, and minimal neuronal regeneration (Tauber et al, ). The notion that fungal brain infections can lead to significant neuronal damage was further supported by a recent set of studies suggesting that Alzheimer's disease might be linked to fungal infection in the brain (Pisa, Alonso, Rabano, Rodal, & Carrasco, ; Soscia et al, ).…”
Section: Introductionmentioning
confidence: 99%